Memoria e historia: acerca de la memoria del dolor y la memoria del rencor (Altre Modernità, 2014)
Starting from different memories as fundamental elements in the configuration of the identity process in individuals and in the culture of the peoples in the diaspora, as well as in mourning processes - normal and pathological - these memories are here analyzed from a psychoanalytical perspective in some contemporary literary works.The first part deals with the memories of resentment, pain, dread, and splendor in the poetical work of Jorge Luis Borges, which is as much a denunciation of the capturing power of that memory of resentment which prevents change, as well as a defense of the liberating memory – memory of splendor -, oriented towards a fraternizing humanity. The reading of the Borgesian work makes it possible to discover certain psychological dynamics that come into play in the configuration of memory and oblivion. The second part of the paper is focused on Amos Oz’ Historia de amor y oscuridad, an example of how these memories are manifested in mass psychology. Particular attention is here paid to the memory of resentment in the complex battles governed by unconscious and conscious  mournings between Arabs and Israelites.